Florence Gétreau, Voir la musique (Paris, Citadelles & Mazenod, 2017) - Duarte, Sónia Maria (Revista Portuguesa de Musicologia, 2020)
Recensão: Florence Gétreau, Voir la musique (Paris, Citadelles & Mazenod, 2017), 417 pp., ISBN: 9782850887192